Analisis Serangan Ransomware Pada Sistem Keamanan Siber Bank Syariah Indoneisa (BSI) Terhadap Customer Turst - Syam Muhaimin; Haslindah; Hasni (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
The development of digital technology has brought significant benefits to the banking industry but has also increased cybersecurity risks, including the threat of ransomware attacks. Bank Syariah Indonesia (BSI) experienced a ransomware attack that affected its operational services and customer trust. This study aims to analyze the impact of the ransomware attack on customer trust at BSI Branch Bone. The research employs a descriptive qualitative approach, with data collected through interviews with customers. The findings indicate that the ransomware attack caused concern among customers, primarily due to delayed information and a lack of transparency from the bank in providing clarification regarding the incident. Most customers felt that BSI did not provide sufficiently detailed information about the impact of the attack on their data security, leading to a decline in trust in the bank. Therefore, this study recommends that BSI enhance its cybersecurity system, improve crisis communication strategies, and increase transparency in handling security incidents to maintain and restore customer trust.